2013
DOI: 10.1176/appi.ps.201100526
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Veterans’ Satisfaction With Examination of Disability From Posttraumatic Stress Disorder

Abstract: Objective The examination to determine if a veteran has service-connected posttraumatic stress disorder (PTSD) affects veterans’ lives for years afterwards. This study examined factors potentially associated with veterans’ perception of their examination’s quality. Methods Three hundred eighty-four veterans participated in a clinical trial in which they received either a semi-structured interview or the examiner’s usual interview. Immediately after the interview, veterans completed confidential ratings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Further, among veterans not meeting diagnostic criteria for SCID PTSD, Black veterans tended to be more likely than White veterans to be denied both C&P PTSD status and PTSD service connection status. These results are consistent with our hypotheses as well as with findings from other studies that have documented racial disparities in VA care (Rosenheck et al, 1995), the amount of compensation given for service connected PTSD (Murdoch et al, 2003), and satisfaction with VA PTSD disability exams (Rosen et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, among veterans not meeting diagnostic criteria for SCID PTSD, Black veterans tended to be more likely than White veterans to be denied both C&P PTSD status and PTSD service connection status. These results are consistent with our hypotheses as well as with findings from other studies that have documented racial disparities in VA care (Rosenheck et al, 1995), the amount of compensation given for service connected PTSD (Murdoch et al, 2003), and satisfaction with VA PTSD disability exams (Rosen et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the influence of veteran racial status on these ratings was not examined. This exclusion is noteworthy, as research both prior to and since the VA OIG investigation has shown that Black veterans receive different VA care than White veterans for a wide range of conditions (Saha et al, 2008); receive less intensive treatment for PTSD specifically (Rosenheck, Fontana, & Cottrol, 1995); are less likely to receive a minimal trial of treatment in the 6 months following PTSD diagnosis (Spoont et al, 2015); are less satisfied with the quality of their PTSD disability examinations (Rosen et al, 2013); and are less likely to be service connected for PTSD, even after controlling for PTSD symptom severity and level of functional impairment (Murdoch, Hodges, Cowper, Fortier, & van Ryn, 2003). These findings suggest that veteran racial status may also influence the outcomes of VA PTSD disability examinations as well as the potential eligibility for disability compensation and other VA benefits.…”
mentioning
confidence: 99%
“…Our finding adds to a growing literature indicating disparities in the experience of service connection exams. Rosen et al [ 29 ] found that Black veterans rated their examinations as lower quality and rated the inter-personal qualities of their examiners lower as compared to White veterans. Especially troubling is Marx et al [ 30 ] finding that PTSD service connection evaluations that did not include psychometric testing appeared to disadvantage Black veterans compared to White veterans.…”
Section: Discussionmentioning
confidence: 99%
“…The research literature emphasizes the need to develop specifically tailored programs and care that can meet the needs of women Veterans, MST survivors, and other vulnerable subpopulations of Veterans, such as LGBT+, Black, Indigenous, and People of Colour. [87][88][89][90][91] The U.S. Department of Veterans Affairs (VA) and its Veterans Health Administration (VHA) have made great strides toward identifying and addressing the needs of women Veterans and, to a lesser extent, the needs of LGBT+ and racialized Veterans through a number of initiatives: dedicated research, 92 designated personnel (e.g., women Veteran coordinators, 93 MST coordinators, 94 and LGBT coordinators 95 ), sex-specific programming and service delivery models, 96 and the use of technology for outreach. 97 The United States stands out for its government-driven and -supported research agenda that covers a wide range of types of research, from biomedical, demographic, and statistical to qualitative, particularly when it comes to women Veterans' health.…”
Section: Tailored Government Supportsmentioning
confidence: 99%